Synergistic Herb-Herb Interaction of the Antinociceptive and Anti-Inflammatory Effects of Syzygium aromaticum and Rosmarinus officinalis Combination - Myrna Déciga-Campos (Hindawi Limited, 2021)
The use of alternative medicine to treat pain has been increased, and the combination of several medicinal plants for its relief is a common practice in traditional medicine. The present study is aimed at determining whether a combination of Syzygium aromaticum (S. aromaticum) and Rosmarinus officinalis L. (R. officinalis) potentiates their antinociceptive and anti-inflammatory effects. These effects were explored using the formalin and carrageenan assays in rats, respectively. Animals received local pretreatment with S. aromaticum oil or R. officinalis ethanolic extract (0.1–100 μg/paw) alone or combined in a 1 : 1 rate. Concentration-response curves were built to compare pharmacological responses after an individual administration of S. aromaticum, R. officinalis, or their combination. The pharmacological interaction was investigated by an isobolographic study using the EC50 of each component in a fixed 1 : 1 ratio. S. aromaticum and R. officinalis administered alone showed significant and concentration-dependent antinociceptive and anti-inflammatory effects, but R. officinalis was more potent than S. aromaticum in both the antinociceptive and anti-inflammatory effects (EC50 = 7.96 ± 0.6 μg/paw vs. EC50 = 41.6 ± 1.7 μg/paw; EC50 = 1.97 ± 0.3 μg/paw vs. EC50 = 26.9 ± 2.5 μg/paw, respectively). The isobolographic analysis of the combination of these species in a 1 : 1 ratio showed a synergistic interaction between S. aromaticum and R. officinalis since Zmix (experimental value) was lower than Zadd (theoretical value) for both the antinociceptive effect (Zmix = 0.45 ± 0.1 < Zadd = 24.8 ± 1.3) and the anti-inflammatory effect (Zmix = 5.2 ± 0.6 < Zadd = 14.4 ± 2.2), suggesting a potentiation for both pharmacological effects. These results prove evidence of the efficacy of mixture herb-herb used in folk medicine for pain therapy. It also emphasizes the requirement of pharmacological studies to explore the efficacy and safety of herb interactions.